Demographic and geographical characteristics of pediatric patients presenting to a convenient clinic at a large railway station in a metropolitan area of Tokyo. Issue 33 (August 2019) - Tsuda, Kenji; Tanimoto, Tetsuya; Hosoda, Kazutaka; Suzuki, Miki; Morohashi, Tamaki; Watanabe, Aika; Takahashi, Kenzo; Kouno, Kaduki; Hamaki, Tamae; Ohnishi, Mutsuko; Kami, Masahiro; Kusumi, Eiji
Abstract : Abstract: There is an increasing demand for medical provision systems that are friendly for working mothers with sick children in Japan. The aim of this cross-sectional, observational study was to analyze the demographic characteristics of pediatric patients presenting to a convenient care clinic, which was located in a large railway station and offered primary care with after-hours accessibility in a metropolitan area of Tokyo. We analyzed anonymous data for patients who had visited the pediatric department at a clinic between August 2013 and June 2016. Data regarding patients' sex, age, time of visit, waiting time, presence or absence of an appointment, diagnosis, and addresses were collected from electronic health and billing records. Overall, 8091 patients visited the department 45, 388 times. The numbers of visits by patients who resided within 2, 5, and 10 miles of the clinic were 37, 160 (84.6%), 42, 336 (96.4%), and 43, 399 (98.8%), respectively. No seasonal variation in the number of visits was observed. Male patients visited the clinic 23, 742 times (52.3%) and the patients' median age was 3 years (interquartile range, 1–6). Most visits occurred on Mondays, and 5643 (15.2%) and 4790 (12.9%) patients visited the clinic when consultations began at 10 AM and 3 PM, respectively. Approximately 20% of weekday visits occurred after 6 PM, when other pediatricians' offices were typically closed. Children older than 7 years of age visited the clinic more frequently after 6 PM. The overall median waiting time was 650 seconds (interquartile range, 429–1020). The 3 most common diagnoses were upper respiratory tract infection (27, 173), asthmatic bronchitis (23, 744), and allergic rhinitis (10, 556). The number of individuals who were referred to other medical institutions was 284 (0.6%). The majority of patients were children aged 1 to 4 years living near the clinic and 80% of visits were during the daytime. However, children older than 7 years of age visited the clinic more frequently after 6 PM. The convenience of the clinic contributed to the fulfillment of the medical needs of children with mild illnesses whose mothers were in full-time employment.